Prevalence and genotypic relatedness of carbapenem resistance among multidrug-resistant P. aeruginosa in tertiary hospitals across Thailand - Khuntayaporn Piyatip; Montakantikul Preecha; Mootsikapun Piroon; Thamlikitkul Visanu; Chomnawang Mullika (BMC, 2012)
Abstract Background Increased infection caused by multidrug resistant (MDR) Pseudomonas aeruginosa has raised awareness of the resistance situation worldwide. Carbapenem resistance among MDR (CR-MDR) P. aeruginosa has become a serious life-threatening problem due to the limited therapeutic options. Therefore, the objectives of this study were to determine the prevalence, the antibiotic susceptibility patterns and the relatedness of CR-MDR P. aeruginosa in tertiary hospitals across Thailand. Methods MDR P. aeruginosa from eight tertiary hospitals across Thailand were collected from 2007-2009. Susceptibility of P. aeruginosa clinical isolates was determined according to the Clinical and Laboratory Standards Institute guideline. Selected CR-MDR P. aeruginosa isolates were genetically analyzed by pulsed-field gel electrophoresis. Results About 261 clinical isolates were identified as MDR P. aeruginosa and approximately 71.65% were found to be CR-MDR P. aeruginosa. The result showed that the meropenem resistance rate was the highest reaching over 50% in every hospitals. Additionally, the type of hospitals was a major factor affecting the resistance rate, as demonstrated by significantly higher CR-MDR rates among university and regional hospitals. The fingerprinting map identified 107 clones with at least 95% similarity. Only 4 clones were detected in more than one hospital. Conclusions Although the antibiotic resistance rate was high, the spreading of CR-MDR was found locally. Specific strains of CR-MDR did not commonly spread from one hospital to another. Importantly, clonal dissemination ratio indicated limited intra-hospital transmission in Thailand.